Simultaneous transcatheter pulmonary and tricuspid valve‐in‐valve implantation for the treatment of failing pulmonary and tricuspid bioprostheses. Issue 7 (28th November 2015) - Baig, Muhammad; Alli, Oluseun; Davies, James
Abstract : We report a case of a patient with a history of bioprosthetic pulmonary and tricuspid valve replacement who developed significant stenosis and regurgitation of the bioprosthetic valves. Due to multiple comorbidities, he was deemed high risk for redo‐valve replacement surgery. He subsequently underwent percutaneous transcatheter pulmonary and tricuspid valve‐in‐valve procedure at the same setting. This is the first of such that is reported in the literature. © 2015 Wiley Periodicals, Inc.